Impacting The Quality of Services and Images of Company To Loyalitas Using BSI Medan City With Provision and Trust of a Variable Intervening - Siti Chairani Zahwa; Sugianto, Sugianto; Tuti Anggraini (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Customer loyalty is very important for the banking business. Loyal customers will not hesitate to spread positive information about the banking services and products they use. Maintaining loyal customers must be a top priority for the banking industry, service quality and company image can be special concerns that banks must pay attention to in maintaining customer loyalty. The aim of this research is to analyze the influence of service quality variables, company image on customer loyalty of Bank Syariah Indonesia (BSI) which is moderated by satisfaction and trust. This research is quantitative research using data collection methods in the form of questionnaires with a Likert scale. The sampling technique in this research is a non-probability sampling technique. The research population is BSI customers who live in Medan City with a sample of 210 people.The results of this research show that the variables of service quality and company image have a positive and significant effect on customer loyalty, as well as through the variables of satisfaction and trust. Indirectly, it can influence service quality and company image on customer loyalty. These findings prove that service quality, company image, customer satisfaction and trust have a very important role in growing customer loyalty at PT Bank Syariah Indonesia Tbk (BSI). Therefore, BSI Bank can develop strategies to increase and retain its customers by considering several aspects in this research.